ANALISIS MISKONSEPSI PESERTA DIDIK KELAS XII MENGGUNAKAN TES DIAGNOSTIK THREE-TIER MULTIPLE CHOICE PADA MATERI HIDROKARBON - Shofiana Shofiana (Program Studi Pendidikan Kimia, FKIP, Universitas Muhammadiyah Cirebon, 2019)
This study aims to identify misconceptions experienced by students in class XII in MAN A and SMAN B in Cirebon City on hydrocarbon material. The research method used is quantitative descriptive method. The sampling technique or subjects used cluster random sampling technique, where the subjects in this study were students of Class XII MIPA 2 in MAN A of the Cirebon City and XII Science 1 in SMAN B of the Cirebon City with the number of students from two schools as many as 45 people. The instrument used is the Three-Tier Multiple Choice Diagnostic Test by categorizing the understanding of concepts possessed by students. The category is divided into three, namely, understanding the concept, not understanding the concept and misconception. The results showed that students in MAN A of the Cirebon City and SMAN B of Cirebon City experienced the highest misconception in the sub-material types of carbon atoms and hydroxide compounds. While the lowest misconception is in the sub-material grouping of hydrocarbon compounds in both schools. The causes of misconceptions of students due to associative thinking, humanistic thinking, incomplete reasoning, students' interest and motivation to learn, abstract chemical concepts, teachers do not optimize learning strategies. Keywords: Misconceptions, Three-Tier Diagnostic Tests, Hydrocarbons